SOME REMARKS ON PERSIAN VARIATIONS IN THE UZBEK LANGUAGE VOCABULARY - Abdulhamid Abduvaliev Abdumominovich (American Journals, 2023)
This article provides detailed information on the use of the affix -ak , meaning smallness, inferiority, deficiency of the vocabulary of the Uzbek language.
Keywords: Lexeme, stem, derivational affix, affixing, noun, adjective, verb, stem, word formation.